2014
DOI: 10.1007/978-1-4939-1031-1_13
|View full text |Cite
|
Sign up to set email alerts
|

Altitude, Attitude and Adaptation

Abstract: The fetus has the extraordinary capacity to respond to stress during development, which, in a large part, is mediated by the hypothalamo- pituitary-adrenal (HPA) axis. Hypoxia represents a significant risk to fetal homeostasis and can occur in a wide range of settings including maternal smoking, preeclampsia, preterm labor and high altitude. To study fetal adaptation to chronic, gestational hypoxia, we developed a model of high-altitude, long-term hypoxia (LTH) in pregnant sheep. We discuss the role of LTH on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…Fetal growth restriction has been observed in women who live, or carry their pregnancy, at high altitude (387), and the risk of developing preeclampsia is higher in these populations than in those nearer to sea level (197). The mechanisms leading to these observations, however, are complex, involving evolutionary adaptations in both placental and maternal cardiovascular function (258,272). The longterm "programming" effects of high altitude on offspring health are not fully understood and would be an interesting area of future study.…”
Section: High Altitudementioning
confidence: 99%
“…Fetal growth restriction has been observed in women who live, or carry their pregnancy, at high altitude (387), and the risk of developing preeclampsia is higher in these populations than in those nearer to sea level (197). The mechanisms leading to these observations, however, are complex, involving evolutionary adaptations in both placental and maternal cardiovascular function (258,272). The longterm "programming" effects of high altitude on offspring health are not fully understood and would be an interesting area of future study.…”
Section: High Altitudementioning
confidence: 99%
“…Among the varied brain structures involved in response strategy choice to the stress of diverse etiology, PVH seems to be the most important structure that regulates HPA activity through CRH secretion [1,2]. It has also been proven with respect to the role of PVH and HPA in adapting to long term hypoxia [20]. The physiological significance of HPA in adaptation mechanisms is determined by the key role of glucocorticoids, which can influence on neuronal plasticity using genomic and non-genomic effects [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that prolonged exposure to HA result in decreased leptin levels (26). However, a large body of research found that HA is associated with increased serum leptin levels (14). A similar contradiction exists in the studies examining serum leptin levels in PE.…”
Section: Discussionmentioning
confidence: 99%